A novel strain-decoupled sensitized FBG temperature sensor and its applications to aircraft thermal management. (August 2021) - Yan, Guang; Wang, Tianqi; Zhu, Lianqing; Meng, Fanyong; Zhuang, Wei
Highlights: A temperature decoupled strain sensor is designed. Realized the temperature measurement of the aircraft cabin. A temperature sensor is sensitized. Abstract: This paper presents a novel type of strain-decoupled sensitized FBG temperature sensor and its applications to accurate aircraft thermal management. After sensitization of the fiber Bragg grating of the sensor, aluminum 7075-T6 is selected as the base material for full-coverage packaging. No direct contact between the packaging position and the structural parts of the fiber Bragg grating is proposed, so as to eliminate the influence of structural deformation on the temperature sensor. The experimental results show that the temperature sensitive speed is 40.4 pm/°C, four times that of the ordinary fiber grating. The deformation of the tensile test piece has no effect on the temperature sensor, which is consistent with the theoretical analysis. The sensor is attached to the aircraft cabin for practical engineering applications. The maximum temperature difference measured by the sensor is at most ±1 °C. This shows that the sensor can be relied on for temperature measurement and that its measurements are accurate enough for actual flight measurements of aircraft load spectrum.